EAST patristic and philosophical and theological culture phenomenon middle ages (Journal of Philosophy Culture and Political Science, 2015)
East patristika is the complete ontologic picture of life including anthropological,cosmological, gnoseological, theological ideas. It reflectson process of philosophical works of religious thinkers and represents acultural, philosophical, religious phenomenon of orthodox outlook. TheByzantine culture was considerably enriched with elements of culture ofthe people of the East that gave it unique color. The contribution of theEastern people to formation and development of the Byzantine civilizationis essential. For Christian dogma there was nothing more dangerous andmore necessary, than systematization of philosophical knowledge for thepurpose of the solution of theological tasks. Orientation of Christian cultureto antique heritage was most of all shown in relation to the most concentratedexpression of the essence of an ellinstvo – philosophy. Fight wasaggravated by the fact, that against Christianity in III-Y of centuries therewere not systems of everyday morals, like stoicism and an epikureizm, butthe original philosophizing about life undertaking to answer deep questionsof human spirit.
Keywords: east patristika; philosophy; process; Christian culture; culture of the people of the East; everyday morals; orientation.